Retrospective analysis evaluating the effect of a keratolytic and physical pretreatment with salicylic acid, urea and curettage on the efficacy and safety of photodynamic therapy of actinic keratoses with methylaminolaevulinate - Gholam, Patrick; Müller-Christmann, Christine; Bosselmann, Ina; Enk, Alexander (Journal of the European Academy of Dermatology and Venereology, 2016)
Background Photodynamic therapy (PDT) is a highly effective treatment option for actinic keratosis (AK). Hyperkeratosis of the AK impairs penetration of the photosensitizer and light and leads to a reduced efficacy of PDT. Therefore, it is commonly recommended to perform curettage of the AK prior to treatment. Objective This observational, monocentric, retrospective study sets out to compare the effects of curettage (CUR), chemical keratolytic pretreatment with salicylic acid 10% (SA), and urea cream 40% (UR) on the efficacy and tolerability of PDT. Method A total of 44 subjects aged 73.2 ± 7.7 years (mean ± SD) with multiple AKs (mean 11.1 per patient) in face and scalp were analysed. In 15 patients, CUR was performed prior to PDT while 15 and 14 patients underwent keratolytic pretreatment with SA and UR, respectively, 1 day prior to PDT. All patients underwent one session of methylaminolaevulinate (MAL) PDT using a 630-nm LED lamp at 37 J/cm2, pain was measured using a visual analogue scale. The response rate was calculated using the documented number of AKs prior and 4 weeks after PDT. Results Mean lesion response rates were 68.5%, 61.4% and 60.8% for CUR, SA and UR respectively. Differences were not significant. Patients with SA or UR experienced significantly more pain (SA: 6.3 ± 2.7, P = 0.02; UR: 6.1 ± 1.8, P = 0.04) than patients with curettage (4.4 ± 2.1). The cosmetic result and the patients' satisfaction 4 weeks after PDT were good to excellent in all three groups without a significant difference. However, pretreatment with SA or UR led to pronounced local reactions compared to CUR. Conclusion Keratolytic therapy with SA or UR is an effective pretreatment for PDT. However, it leads to an increase in pain during PDT and pronounced local reactions.
Accepted: 4 September 2015
Gesehen am 05.06.2020